STATUS AND DEVELOPMENT OF RUNWAY OVERRUN PREVENTION SYSTEMS - A. V. Mozolyako; A. N. Akimov; V. V. Vorobyev (Научный вестник МГТУ ГА, 2016)
This article describes the current condition of the onboard braking systems while rolling and the approach to the construction of the aircraft automatic braking system. The article analysis the main reasons for RW overrun and measures of reducing the risk.